2011
DOI: 10.1177/1753193410396648
|View full text |Cite
|
Sign up to set email alerts
|

Which instrument should we use to assess hand function after digital replantation?

Abstract: The functional recovery of a replanted body part is as important as its viability. We compared four instruments frequently used for the evaluation of hand function after digital replantation. The functional results of 17 patients at least one year after replantation of a total digital amputation between 2004 and 2007 were evaluated according to the Tamai, Ipsen, Chen and Disabilities of the Arm, Shoulder and Hand questionnaires. Scores of each patient for each test were calculated and intra-individual comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…DASH or Quick-DASH have been used in other replantation studies and reported values are the same as in this study [2,13]. However, other reported higher DASH scores, which might reflect different follow up times and different patient selection [11,42]. …”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…DASH or Quick-DASH have been used in other replantation studies and reported values are the same as in this study [2,13]. However, other reported higher DASH scores, which might reflect different follow up times and different patient selection [11,42]. …”
Section: Discussionsupporting
confidence: 50%
“…However, the EQ-5D has not before been used in this patient group. Hand function has been evaluated previously by different types of scores [2,8,11,13,14,42]. Quality of life is more than hand function.…”
Section: Discussionmentioning
confidence: 99%
“…This scoring method relies on the surgeon’s assessment of the patient’s use of the limb, based on 4 objective criteria: sensation, range of motion, Medical Research Council (MRC) power grade, and global use of the affected extremity. 15 , 16 Replantations are then rated as grade I (excellent), grade II (good), grade III (fair), and grade IV (poor). A summary of the Chen criteria can be found in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The TAMAI score involves the measurement of joint range of motion, ability to perform activities of daily living, subjective symptoms, patient overall satisfaction, and job status. 16 , 17 Of the 11 cases graded using the TAMAI scoring, 1 patient had a poor outcome (9%), 5 with a fair outcome (45%), and 5 more with a good outcome (45%). 14 …”
Section: Resultsmentioning
confidence: 99%
“…Although the Chen functional grade has not been validated, it is used widely to evaluate results after hand replantation. However, it was not our main outcome measure because a good correlation between the DASH score and the Chen functional grade is yet to be determined after replantation [56]. The mean HTSS values indicated the results for the allograft and patient function to be good.…”
Section: Discussionmentioning
confidence: 99%